Measuring the consistency of national accounts and balance of payments statistics - Robert Obrzut (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2019)
Since the adoption of new methodological standards for European national accounts and balance of payments (BoP) statistics in 2014, both statistical domains should be directly comparable and fully consistent. The latter implies that data elements that describe the same economic phenomena related to a specific point-in -time should be identical, and refrain from sending contradictory messages to the user. Hence, in applying both methodologies respectively, the European system of accounts 2010 (ESA 2010) and the Balance of Payments and International Investment Position Manual - Sixth Edition (BPM6), a high degree of comparability and consistency between the account for the rest of the world (RoW) and the balance of payments is not only envisaged but should be manifested in quantitative measures of consistency.Since the introduction ESA 2010 and BPM6 it has been essential for Eurostat to monitor whether data are indeed consistent, and where inconsistencies occur, ascertain which accounts were most concerned, which EU Member States were most concerned, and what actually caused the measured discrepancies. Over time, quantitative analyses and investigations have resulted in the identification of the underlying causes for inconsistencies between sector accounts and the balance of payments (Obrzut (2017)).From 2019, both statistical domains will be undergoing fundamental revisions by national compilers (benchmark revisions): their endeavours for better quality and more comparable statistics shall be guided by the full implementation of the above mentioned consistency requirements. Therefore, conclusive quantitative measures should assist decision-makers, quality audits and external users in obtaining a good indication as to how effective these oncoming revision processes for the statistics of EU Member States will be in terms of leading to the full adoption of the requirements of the methodological standards.In this article, concepts and approaches to measure consistency between national accounts and the balance of payments are presented, and consequently a scoreboard of indicators based on mean absolute percentage deviation measures is proposed to produce a rough, but conclusive view on the state of consistency among the statistics of EU Member States.
Keywords: 330; balance of payments; sector accounts; international trade; data consistency